Modified full bridge dual inductive coupling resonant converter for electric vehicle battery charging applications - Kondreddy Sreekanth Reddy; Sreenivasappa Bhupasandra Veeranna (Institute of Advanced Engineering and Science, 2022)
In this paper, a modified full bridge dual inductive coupling (LCL) resonant converter for electric vehicles (EVs) battery charging applications is proposed. The main objective of the proposed topology is to operate the converter in constant voltage (CV) and constant current (CC) mode during battery charging. The presented topology's uniqueness comprises the following: i) isolated charging and power factor correction (PFC), ii) to achieve zero-voltage switching (ZVS) and zero-current switching (ZCS) for inverter switches, iii) reduction of number of rectifier diodes to reduce the conduction and switching losses, and iv) reducing the magnetizing current. The output voltage dependence of resonant converter is reduced using a PFC converter against the variations of the alternating current (AC) grid input voltage. The variations of the wide range output voltage and load is compensated by a small variation in switching frequency. The proposed topology's detailed operation is simulated using the MATLAB/Simulink tool.